The Relationship Between Breastfeeding and Weight Status in a National Sample of Australian Children and Adolescents - Scott, Jane; Ng, S.; Cobiac, L. (BioMed Central Ltd, 2012)
Background: Breastfeeding has been shown consistently in observational studies to be protective of overweight and obesity in later life. This study aimed to investigate the association between breastfeeding duration and weight status in a national sample of Australian children and adolescents.Methods: A secondary analysis of the 2007 Australian National Children’s Nutrition and Physical Activity Survey data involving 2066, males and females aged 9 to 16 years from all Australian states and territories. The effect of breastfeeding duration on weight status was estimated using multivariate logistic regression analysis.Results: Compared to those who were never breastfed, children breastfed for =6 months were significantly less likely to be overweight (adjusted odds ratio: 0.64, 95%CI: 0.45, 0.91) or obese (adjusted odds ratio: 0.51, 95%CI: 0.29, 0.90) in later childhood, after adjustment for maternal characteristics (age, education and ethnicity) and children’s age, gender, mean energy intake, level of moderate and vigorous physical activity, screen time and sleep duration.Conclusions: Breastfeeding for 6 or more months appears to be protective against later overweight and obesity in this population of Australian children. The beneficial short-term health outcomes of breastfeeding for the infant are well recognised and this study provides further observational evidence of a potential long-term health outcome and additional justification for the continued support and promotion of breastfeeding to six months and beyond.